THE "CREATIVE HOURS" MODEL BASED ON THE LEARNING CYCLE AS A VEHICLE FOR THE GROWTH OF STUDENTS' ENTREPRENEURIAL SPIRIT: A CASE STUDY AT SANTA URSULA JUNIOR HIGH SCHOOL BANDUNG - Maria Lufransiya Bribin; Dadang Sundawa; Asep Mahpudz; Daud Yefkanius Nassa (SOSIOEDUKASI, 2026)
This study aims to describe and analyze the “Creative Hours” learning model centered on a learning cycle as a vehicle for cultivating the entrepreneurial spirit of students in an entrepreneurship-based school. A qualitative approach with a case study design was employed at SMP Santa Ursula Bandung. Data were gathered through participant observation, in-depth interviews with the entrepreneurship team, accompanying teachers, and the principal, as well as documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings show that the “Creative Hours” model rests on three components curriculum, process, and evaluation operationalized through five learning-cycle stages: exploring, planning, doing, communicating, and reflecting. Across these stages the school instills fifteen entrepreneurial values that can be grouped into self-regulation values, creative-innovative values, social-collaborative values, perseverance values, and honesty as a moral anchor. The model’s distinctiveness lies in a 60% weighting for character assessment that exceeds the weighting for knowledge and skills, the integration of the entrepreneurship curriculum with the school’s core values, and the presence of an authentic audience (parents) at the communication stage. The study concludes that a structured, character-oriented learning cycle functions effectively as a vehicle for cultivating entrepreneurial spirit and can serve as a reference model for developing entrepreneurship-based learning in other educational units.